How servant leadership motivates young university teachers’ workplace well-being: The role of occupational commitment and risk perception - Zeng, Jianji; Lai, Jiahui; Liu, Xiaofan (Frontiers in Psychology, 2022)
Drawing on the integration of social exchange theory and situational power theory, this paper explores the effect of servant leadership on young university teachers’ workplace well-being and explores the mediating effect of occupational commitment and the moderating effect of risk perception on the indirect effects of servant leadership on workplace well-being. A questionnaire was distributed using the Questionnaire Star online questionnaire platform and a two-wave time-lagged design was used to collect 215 survey samples of young teachers from Chinese higher education institutions. SPSS 23.0 was used to test the hypothesized relationship between the variables. Results revealed that servant leadership was positively related to young university teachers’ workplace well-being. Occupational commitment plays a partial mediating role in linking servant leadership and young university teachers’ workplace well-being. Risk perception plays a moderating role in the indirect relationship between servant leadership, occupational commitment, and workplace well-being. When risk perception has a low level, the mediating effect of occupational commitment is stronger.